2008
DOI: 10.1029/2007tc002169
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modeling of frontal and basal accretion at collisional margins

Abstract: We investigate the deformation of orogenic wedges that form in the early stages of continent‐continent collisions using a two‐dimensional numerical model limited to the upper lithosphere. Our models show that deformation at the plate margins is influenced by rheology, surface processes, and the balance between inward mass flux and outward subduction flux, as controlled by the subduction load (which represents the effects of slab pull and resistive forces) and flexural downbending. We find three characteristic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 71 publications
(103 reference statements)
2
27
0
Order By: Relevance
“…[144] explain this change by the effect of the crustal root beneath the Alps, which induces a component of gravity spreading in the uppermost part of the orogen. In fact, numerical modeling also show that such an extension parallel to the overall contraction develops in the core of model orogens as a consequence of gravitational spreading [39,55].…”
Section: Central Alps Of Switzerlandmentioning
confidence: 99%
See 3 more Smart Citations
“…[144] explain this change by the effect of the crustal root beneath the Alps, which induces a component of gravity spreading in the uppermost part of the orogen. In fact, numerical modeling also show that such an extension parallel to the overall contraction develops in the core of model orogens as a consequence of gravitational spreading [39,55].…”
Section: Central Alps Of Switzerlandmentioning
confidence: 99%
“…[39] discuss the importance of erosion and could show that basal accretion is directly linked to erosion.…”
Section: Frontal and Basal Accretionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nappe stacking increases the volume of the orogen with rock material being accreted at its front and base. [44] studied the factors influencing frontal and basal accretion at collisional margins by numerical modeling and found that the most influential factors are the rheology of the material, surface processes and the balance between inward and outward material flux. These models suggest that a mechanically strong crust with almost fully brittle material behavior develops frontal and basal accretion, which occur independently and spatially separated.…”
Section: Frontal and Basal Accretionmentioning
confidence: 99%